Hygrothermal performance of a vapor-open envelope for subtropical climate, field test and model validation. (December 2016) - Goto, Yutaka; Ghazi Wakili, Karim; Ostermeyer, York; Sasic Kalagasidis, Angela; Wallbaum, Holger
Abstract: The construction industry is known to be a key contributor to manmade climate change. Amongst other nations, Japan has a building energy efficiency goal which does not yet emphasize the importance of the moisture safety design of well-insulated building envelopes considering its diverse climatic conditions. The authors developed a vapor-open wooden building envelope for the subtropical conditions of Japan and optimized a design method, which considers environmental, economic and hygrothermal aspects. As a case study, a detached residential building has been constructed in Ohmihachiman (central Japan). The building has been monitored using a large number of temperature and humidity sensors inside the walls and the roof. Results have been obtained from measurements over a period of one year. Furthermore, transient hygrothermal simulations using the measured exterior and interior climates have been carried out. It was shown that 1) the construction of the wall was successful with the desired level of air-tightness and 2) the simulation model by a commercial software is applicable for predicting the hygrothermal performance of the wall with the envelope system in the actual use condition. Highlights: A vapor-open wooden building envelope for subtropical conditions was applied to a residential building in central Japan. An insulation optimization design scheme was applied considering environmental, economic and hygrothermal aspects. The building has been monitored using a large number of temperature and humidity sensors inside the walls and the roof. The hygrothermal performance of the envelope was validated by the measurements and transient heat and moisture simulations. It was shown that the model can simulate the hygrothermal behavior of the envelope with a high accuracy.